Penyuluhan dan Pemulihan Hunian untuk Korban Gempa Cianjur - Farida Farida; Tanjung Prasetyo; Kasman Kasman (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Cianjur Regency was hit by an earthquake with a magnitude (M) of 5.6 which caused casualties and damage to public facilities and residences. Temporary shelter is the government's response in disaster mitigation however, emergency shelter is still the main thing when a disaster occurs. Emergency shelter that can be provided during a disaster is like an emergency tent. However, the available emergency tents are not proper and up to standard and have not stood in the appropriate position. The purpose of this service is to provide Counseling and Residential Restoration for Cianjur Earthquake Victims. Counseling on disaster mitigation and shelter restoration by setting up appropriate emergency tents as a solution for victims who have had to flee due to trauma and whose houses have been damaged or even destroyed. The result of the activity was that the participants understood disaster mitigation and residents' housing recovery by setting up emergency tents that could accommodate the temporary shelter needs of the victims. Adequate emergency tents with bright colors, windows for air circulation and insulation so that refugees can live separately so as to address social, health and psychological problems. Emergency tents can also be used to accommodate aid that comes from other parties, in addition to being used for children's playgrounds, community gathering places, and places of worship.